ChemInform Abstract: Optically Transparent Water Oxidation Catalysts Based on Copper Nanowires. Issue 13 (1st April 2014) - Chen, Zuofeng; Rathmell, Aaron R.; Ye, Shengrong; Wilson, Adria R.; Wiley Benjamin J., Wiley Benjamin J.
Abstract Transparent catalysts for water oxidation are created by electrodeposition of nickel or cobalt around a conducting network of copper nanowires.